PENGARUH LITERASI KEUANGAN, SIKAP LOVE OF MONEY, DAN PENGETAHUAN LAPORAN KEUANGAN TERHADAP PERILAKU PENGELOLAAN KEUANGAN UMKM DI WILAYAH KABUPATEN SUBANG - Irwan Fathurrahman; Icih Icih; Asep Kurniawan (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2020)
Many Micro, Small, Medium Enterprises (MSMEs) in Indonesia still do not conduct financial management behavior or there is no financial separation between business money and daily necessities. This study aims to determine the effect of financial literacy, love of money attitudes, and knowledge of financial statements on the behavior of financial management umkm in the Subang Regency. The population used in this research is MSME type of microbusiness in the area of ​​Subang Regency. The sampling technique used in this study is the